Implementation Of Service Excellence In The Field Of Laundry Services To Customer Satisfaction In Aa Laundry Cikarang - Agus Podo Suseno; Febriansyah Febriansyah; Ahmad Azmy (Dinasti Publisher, 2025)
The laundry service industry growing rapidly along with the demands of people's increasingly practical lifestyles. In thiscompetitive business environment, the implementation Service excellenceis a key factor to maintain customer satisfaction. This study aims to analyze the effect of the implementation Service excellence on customer satisfaction in the service industry. approachused in this study, by collecting and analyzing various literature sources related to the concept Service excellence and customer satisfaction. Data sources used include scientific journals, books, and the results of previous research. The analysis was done descriptively to obtain a deep understanding of the relationship between the implementation Service excellenceand customer satisfaction. The results showed that the dimensions Service excellence, which consists ofspeed and accuracy of service, quality of laundry, friendliness and professionalism, access and flexibility, effective complaint handling, choice of fragrance, have a positive and significant influence on customer satisfaction in the service industry. The managerial implication of this study is that it is important for service providersto focus on improving service quality in order to achieve optimal customer satisfaction.